The Ant Empire: Fintech Media and Corporate Convergence within and beyond Alibaba - Wang, Jing; Doan, Mai Anh (The Political Economy of Communication, 2019)
Data-driven technologies and platform economies have been widely employed by Chinese companies in a variety of business sectors. In the past decade, these digital applications have profoundly restructured economic development and power relations in Chinese society. This article examines how the promotions of fintech media and communication technologies for transactions, loans, investments and many other financial practices–engender and enlarge Alibaba's digital financial platform, Ant Financial, the largest digital financial company in China. From a political economy of communication perspective, we consider Ant Financial as a product of data-centric corporate convergence in which fintech media have extracted user data from Alibaba's e-commerce and digital payment platforms and utilized this data to drive Alibaba's growth in financial businesses. The consolidation of multiple platforms has transformed financial industries, challenged policy and regulatory regimes, and reshaped the cultures of finance in China. The convergence paradigm underpins the digital, technology-driven logic facilitated by the state in resource allocation and policy-making. The government's supportive role is a vital condition for the rise of Chinese fintech giants such as Baidu Finance, Ant Financial, Tencent Finance, and Jingdong Finance.